2021
DOI: 10.1155/2021/4154381
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Phenolics (Bound and Free), Minerals, and Antioxidant Activity of Twenty-Eight Wild Edible Fruits of Twenty-Three Species from Far North Region of Cameroon

Abstract: The present study is aimed at investigating the variation of phenolics (bound and free), minerals, and antioxidant potentials of the wild edible fruits (fresh and dry) native from Far North Region of Cameroon. The results showed significant ( p < 0.01 ) differences among fruits and species for all parameters. Bound phenolic content (mgGAE/100 g) of dry fruits (DF) ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(62 reference statements)
0
1
1
Order By: Relevance
“…The results of the phytochemicals study revealed the presence of polyphenols, flavonoids, and tanins. The values of total polyphenols, total flavonoids, and total tannins were higher than the values obtained by Koubala et al [ 47 ] in some wild edible fruits from the far north region of Cameroon. The presence of those compounds in B. aegyptica pulp fruit could partly explain the pharmacological properties obtained in the present study.…”
Section: Discussioncontrasting
confidence: 80%
“…The results of the phytochemicals study revealed the presence of polyphenols, flavonoids, and tanins. The values of total polyphenols, total flavonoids, and total tannins were higher than the values obtained by Koubala et al [ 47 ] in some wild edible fruits from the far north region of Cameroon. The presence of those compounds in B. aegyptica pulp fruit could partly explain the pharmacological properties obtained in the present study.…”
Section: Discussioncontrasting
confidence: 80%
“…The intake of antioxidants from food could limit the negative effects of ROS and RNS by inhibiting their action [135]. The main compounds from plants that have antioxidant properties are polyphenols like phenolic acids, flavonoids, anthocyanins, lignans and stilbenes, terpenes and terpenoids, vitamins like E and C [135], and some minerals such as zinc, copper, and selenium [136][137][138]. Some of these compounds, especially polyphenols, and carotenoids (tetraterpenoids), also have "anti-inflammatory, antibacterial, antiviral, anti-aging, and anticarcinogenic properties" [135].…”
Section: Effects Of Extrusion On the Biological Activitymentioning
confidence: 99%
“…In dry fruits, bound phenolic content (mgGAE/100 g) ranged from 96 to 408; and free phenolic from 46 to 345. While in fresh fruits, the bound phenolic content ranged from 29 to 306; and free phenolics from 120 to 316 [ 63 ]. The main difference between free and bound phenolics is that free is solvent extractable, while the bound phenolic cannot be extracted into water or aqueous/organic solvents mixtures [ 60 ].…”
Section: Hhp As a Stress Factor For The Biosynthesis Of Phenolics And...mentioning
confidence: 99%